(untitled) (Malay Literature, 2025)
Neuroticism is a personality trait associated with an individual’s tendency to experience extreme anxiety, tension and fear. This condition occurs due to specific reasons and usually in high-stress situations, as depicted in literary works such as psychological thriller novels. However, research on neuroticism in literature remains a significant gap. This study’s objective aims to examine the causes and effects of neuroticism and how it is addressed through a comparative analysis of characters found in two psychological thriller novels, namely Rahsia Perindu (2005) by Malaysian author Ramlee Awang Murshid and The Silent Patient (2019) by English author Alex Michaelides. This study uses textual analysis to compare both novels, guided by Paul Costa and Robert McRae’s (1992) Big Five Personality Theory as the framework. The findings reveal that neuroticism in the two novels stems from depression, hostility, extreme anxiety and exposure to stress. The consequences of neuroticism often involve the impulsive drive to murder. Both novels present different approaches to coping with neuroticism, shaped by the characters’ respective culture, teachings, religion and environment. This study is important in highlighting the thoughts and creativity of Malaysian and English authors in portraying neuroticism in their works. It is also important in serving as a guide for readers to understand neuroticism and psychological issues on a broader scale while contributing to interdisciplinary literary research. Full text: PDF